Economic Modernization And Structural Reform Of Uzbekistan - Po‘latov, Odil; Imomova, Yulduzkhon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
Uzbekistan’s modernization agenda is anchored in a broad reform program initiated after President Mirziyoyev’s 2016 election. Since 2017, the country has undertaken “wide-ranging political and economic reforms” to liberalize markets and improve the business climate. Modernizing and diversifying Uzbekistan’s leading industries, while reducing state dominance is the aim. This marks a shift from prior emphasis on cotton cultivation and gold mining.  The objective of this paper is to analyze the key obstacles to the modernization of Uzbekistan and to propose feasible and practical solutions across economic endeavors that correspond to Uzbekistan’s national development goals and “New Uzbekistan Concept”.